Moderasi Kesadaran Pajak Pada Moral Pajak, Pemeriksaan, Dan Sanksi Terhadap Kepatuhan UMKM - Darmayasa, I Nyoman; Putu Ayu Rita Pariani; I Nyoman Mandia, (Jurnal Pajak dan Keuangan Negara (PKN), 2022)
This study aims to determine the effect of tax morals, tax audits, sanctions, and moderation of tax awareness on tax compliance for micro small and medium enterprises (SMEs). This study analyzed primary data questionnaires from 150 answers of SMEs respondents registered at the Bali Regional Tax Service Office. Testing the research variables using multiple linear regression analysis and moderated regression analysis (MRA). Tax morals, tax audits, and sanctions had a positive and significant effect on SMEs compliance. Whereas MRA testing shows that tax awareness moderates the moral relations of tax and tax audits of SMEs compliance. However, tax awareness cannot moderate the relationship between sanctions towards SMEs compliance which is influenced by psychological factors of SMEs that are affected by the covid-19 pandemic. SMEs prioritizes the sustainability of its business rather than meeting tax compliance during the pandemic. The limitation of the research is that SMEs have not been classified according to SMEs affected or not affected by the pandemic. The contribution of research related to the psychological aspect of SMEs during the pandemic can be a consideration for tax authorities to formulate tax policies. Penelitian ini menguji pengaruh moral pajak, pemeriksaan pajak, sanksi, dan moderasi kesadaran pajak terhadap kepatuhan pajak bagi usaha mikro kecil dan menengah (UMKM). Penelitian ini menganalisis data primer kuesioner dari 150 jawaban responden UMKM yang terdaftar di Kantor Pelayanan Pajak Daerah Bali. Pengujian variabel penelitian menggunakan analisis regresi linier berganda dan moderated regression analysis (MRA). Moral pajak, pemeriksaan pajak, dan sanksi berpengaruh positif terhadap kepatuhan UMKM. Sedangkan, pengujian MRA menunjukkan bahwa kesadaran pajak memoderasi hubungan moral pajak dan pemeriksaan pajak terhadap kepatuhan UMKM. Namun, kesadaran pajak tidak memoderasi hubungan sanksi terhadap kepatuhan UMKM yang dipengaruhi oleh faktor psikologis UMKM yang terkena dampak pandemi covid-19. UMKM mengutamakan keberlanjutan usahanya daripada memenuhi kepatuhan pajak di masa pandemi. Hasil penelitian diharapkan menjadi pertimbangan otoritas pajak untuk memformulasikan kebijakan perpajakan kedepannya.